COLOUR: REVEALS YOUR PERSONALITY - Singh Chauhan, Bijender (International Journal of Research -GRANTHAALAYAH, 2014)
Colours are forces radiant energies that affect us positively or negatively, whether we are aware of it or not in our daily life. The effects of colours should be experienced and understood not only but also psychologically and symbolically. This paper investigates the various effects of light and colours on our visual apparatus –eye and brain and their anatomical relationships and functions. This paper describes the influence of colour radiation on our mind and spirit. Discovery of relationships, mediated by the eye and brain is major concern of my studies. Paper describes colour perception and colour aesthetic in three directions: 1) Impression (visually) 2) Expression (emotionally) 3) Construction (symbolically).